OVERCOMING PRONUNCIATION IN ENGLISH LANGUAGE LEARNING USING BINGO GAMES - Warda Anggraeni; Handi Pabriana (Journal of English Educational Study (JEES), 2026)
Pronunciation remains a persistent challenge for Indonesian EFL learners, particularly for Sundanese-speaking students who often struggle to distinguish English phonemes such as /p/, /f/, and /v/ due to first language interference. While previous studies have highlighted the benefits of game-based learning, there is limited research on the use of Bingo games specifically for targeted phonological intervention in this context. This study aims to bridge this gap by investigating the effectiveness of Bingo games in improving the pronunciation skills of fifth-grade students in West Java. Employing a mixed-method Classroom Action Research (CAR) design, the study involved 19 students and was conducted in two cycles, each comprising planning, acting, observing, and reflecting phases. Pronunciation assessments (pre-test and post-test), along with observational notes and additional documentation, were utilized to gather data. The results demonstrated significant improvements in students’ ability to distinguish and pronounce /p/, /f/, and /v/ after the Bingo game intervention, with average post-test scores increasing in both cycles. Observation data further revealed enhanced student engagement, enthusiasm, and classroom participation, especially in the second cycle following instructional refinements. These findings suggest that integrating Bingo games into English lessons can effectively address specific pronunciation difficulties while fostering a more interactive and motivating learning environment. The study recommends that teachers adopt game-based strategies like Bingo to support pronunciation development and calls for further research into long-term impacts and adaptations for diverse learner needs